Disruption of the brain-derived neurotrophic factor (BDNF) immunoreactivity in the human Kölliker-Fuse nucleus in victims of unexplained fetal and infant death - Lavezzi, Anna M.; Corna, Melissa F.; Matturri, Luigi (Frontiers in Human Neuroscience, 2014)
Experimental studies have demonstrated that the neurotrophin brain-derived neutrophic factor (BDNF) is required for the appropriate development of the central respiratory network, a neuronal complex in the brainstem of vital importance to sustaining life. The pontine Kölliker-Fuse nucleus (KFN) is a fundamental component of this circuitry with strong implications in the pre- and postnatal breathing control. This study provides detailed account for the cytoarchitecture, the physiology and the BDNF behaviour of the human KFN in perinatal age. We applied immunohistochemistry in formalin-fixed and paraffin-embedded brainstem samples (from 45 fetuses and newborns died of both known and unknown causes), to analyze BDNF, gliosis and apoptosis patterns of manifestation. The KFN showed clear signs of developmental immaturity, prevalently associated to BDNF altered expression, in high percentages of sudden intrauterine unexplained death syndrome (SIUDS) and sudden infant death syndrome (SIDS) victims. Our results indicate that BDNF pathway dysfunctions can derange the normal KFN development so preventing the breathing control in the sudden perinatal death. The data presented here are also relevant to a better understanding of how the BDNF expression in the KFN can be involved in several human respiratory pathologies such as the Rett’s and the congenital central hypoventilation syndromes.